ANALYSIS OF COMPETITIVENESS FOR MARKET SHARE EXPANSION OF PT BANK JAGO TBK - Hendri Khuan (International Journal Labs, 2022)
The Bank Jago is a commercial bank that should continue to provide the services in global competitiveness. The Bank Jago should continue to innovate and use the latest technology to excel in competition in the industry. Bank Jago collaborating with the e-commerce and lending ecosystem to provide digital financial services in the middle and mass-market segments that have not been fully served so far. The research is suggested that Bank Jago should make improvements to business processes identified as weaknesses because they can obscure their strengths, and Bank Jago should also evaluate the price of service solutions by considering the value of their products and the dynamics of market prices.